Highly diastereoselective alkylation of vicinal dianions of chiral succinic acid derivatives: A new general strategy to (R)-β-arylmethyl-γ- butyrolactones - Manat Pohmakotr (2018)
The vicinal dianions derived from chiral succinic acid derivatives, 1,4-bis[(4R,5S)-3,4-dimethyl-2-oxo-5-phenylimidazolidin-1-yl]butane-1,4-dione and 1,4-bis[(4S,5R)-3,4-dimethyl-2-oxo-5-phenylimidazolidin-1-yl]butane-1,4- dione react with arylmethyl bromides with high diastereo- and regio-selectivity to provide the corresponding chiral α-arylmethylated succinic acid derivatives; the (R)-products are converted into (R)-β-arylmethyl-γ- butyrolactones and (R)-α-arylmethyl-γ-butyrolactones. © 2004 Elsevier Ltd. All rights reserved.